Adjunct Antihyperglycemic Agents in Overweight and Obese Adults With Type 1 Diabetes. Issue 4 (April 2019) - Isaacs, Diana; Yager, Stephanie; Parker, Marcie; Wolfe, Lauren; Luxenburg, Jennifer; Lekic, Sanela
Objective: People with type 1 diabetes often have suboptimal glycemic control. The gold standard of treatment is basal-bolus insulin or subcutaneous insulin infusion via insulin pump. Although insulin therapy improves glycemic control, weight gain and hypoglycemia often limit achievement of hemoglobin A1C (A1C) goals. The number of people with type 1 diabetes who are overweight or obese is increasing, and there are many similarities between what was historically called type 1 and type 2 diabetes. Therefore, there is rationale for using antihyperglycemic agents that target other pathophysiological abnormalities to facilitate weight loss and improve glycemic control.Data Sources: We performed a MEDLINE search from 1975 through October 2018 to identify articles that studied noninsulin agents in adults with type 1 diabetes and body mass index (BMI) ≥25 kg/m 2 .Study Selection and Data Extraction: Identified articles were included if the study duration was ≥4 weeks, included ≥20 patients, and set mean baseline BMI ⩾25kg/m 2 .Data Synthesis : This review summarizes 32 clinical trials. Amylin mimetics, sodium-glucose-like transporter-2 inhibitors, and glucagon-like-peptide-1 receptor agonists demonstrate the greatest improvements in body weight and A1C. The most common adverse effects are hypoglycemia and ketosis.Relevance to Patient Care and Clinical Practice: Patients with type 1 diabetes may have interest in starting noninsulin agents. Clinicians need to be knowledgeable in the efficacy and adverse effect profile of these agents, specifically in people with type 1 diabetes.Conclusions : Adding noninsulin antihyperglycemic agents may benefit select overweight or obese adults with type 1 diabetes. These agents are off-label, and if used, close monitoring is essential.